The girls of August - Siddons, Anne Rivers (Grand Central Publishing, 2014)
"Every August, four women would gather together to spend a week at the beach, renting a new house each year. The ritual began when they were in their twenties and their husbands were in medical school, and became a mainstay of every summer thereafter. Their only criteria was oceanfront and isolation, their only desire to strengthen their far-flung friendships. They called themselves the Girls of August. But when one of the Girls dies tragically, the group slowly drifts apart and their vacations together are brought to a halt. Years later, a new marriage reunites them and they decide to come together once again on a remote barrier island off the South Carolina coast. There, far from civilization, the women make startling discoveries that will change them in ways they never expected" --